Application of Meir-Keeler’s Fixed Point Theorem for Existence Result of Non-Instantaneous Impulsive Integro-Differential Equations with Infinite Delay - Mokhtari, Sara; Bouteffal, Zohra; Salim, Abdelkrim; Benchohra, Mouffak (Discontinuity, Nonlinearity, and Complexity, 2026)
This paper tackles some existence results for semilinear integro-differential equations with non-instantaneous impulsions on a finite interval via resolvent operators. Our criteria, obtained by applying a new fixed point theorem with respect to Meir-Keeler condensing operators. The obtained result is illustrated by an example at the end.